2023
DOI: 10.1002/jhbp.1319
|View full text |Cite
|
Sign up to set email alerts
|

Validation of quantitative prognostic prediction using ADV score for resection of hepatocellular carcinoma: A Korea–Japan collaborative study with 9200 patients

Abstract: BackgroundA score derived from the concentrations of α‐fetoprotein (AFP) and des‐γ‐carboxy prothrombin (DCP) and tumor volume (TV), called ADV score, has been shown to be prognostic of hepatocellular carcinoma (HCC) recurrence following hepatic resection (HR) or liver transplantation.MethodsThis multicenter, multinational validation study included 9200 patients who underwent HR from 2010 to 2017 at 10 Korean and 73 Japanese centers, and were followed up until 2020.ResultsAFP, DCP, and TV showed weak correlatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
(127 reference statements)
0
3
0
Order By: Relevance
“…Survival analysis indicated that both MVI and an ADV score exceeding 4.2log resulted in comparable DFS and OS outcomes. These findings suggest the practicality of employing a preoperative diagnostic approach utilizing an ADV score cutoff of 4.2log for predicting the presence of MVI [10].…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Survival analysis indicated that both MVI and an ADV score exceeding 4.2log resulted in comparable DFS and OS outcomes. These findings suggest the practicality of employing a preoperative diagnostic approach utilizing an ADV score cutoff of 4.2log for predicting the presence of MVI [10].…”
Section: Discussionmentioning
confidence: 85%
“…A composite score, known as the ADV score, which is calculated by multiplying the levels of α-fetoprotein (AFP) and des-γ-carboxy prothrombin (DCP), alternatively referred to as proteins induced by vitamin K antagonist or absence-II (PIVKA-II), along with tumor volume (TV), has been demonstrated as an all-encompassing prognostic indicator for HCC subsequent to HR or LT [2][3][4][5][6][7][8][9][10][11][12][13]. This ADV score serves as a quantifiable metric that reflects the underlying characteristics of the tumor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation